Pengaruh Perbedaan Perspektif Tiap Generasi Terhadap Keberhasilan Suksesi Pada Bisnis Keluarga - Raja Daud Pratama; Erica Adriana (Politeknik Kampar, 2023)
Succession is a topic that is never separated from the scope of the family business. This study aims to understand the effect of different perspectives from each generation on the success of the succession process in family businesses. Besides that, we can also understand what factors arise when there are differences in perspectives between generations. The model of this research is a literature study that uses references to previous research journals. The result is that many internal factors influence the success of the succession process in a family business. The differences in this perspective can be seen in several aspects such as vision and mission, business strategy, product innovation, corporate governance, organizational culture, leadership style, communication, collaboration, conflict, motivation, and expectations. Besides the many ways of looking at these aspects, there is a positive impact that arises, namely the diversity of views.